Elite Rationality, Traditions and Pragmatic Politicians - Pradana, Mahatva Yoga Adi (Journal of Politics and Policy, 2020)
The political elite move is a common phenomenon when elections will take place. Where the behavior of the converted elite has even become tradition. Look at the phenomena that occur in Indonesia today. The political elites seemed to be looking for a shortcut to gain power easily. Look for populist figures to lift personal imagery for an interest. The realization of the strategy was done by changing the party suit with all the ideology and rationality of his thinking. Even the displaced elites must willingly put off his identity as an idealistic politician in order to accommodate their political interests. Various political strategies were made by making noise by raising political content and hoax preaching. This article seeks to see how closely the political elites think with pragmatism politics through its political traditions and strategies. In addition to the current digital age, the elite behavior creates a new political space with accommodation issues that are not necessarily the truth by raising alternative facts to form new truths. This is the post-truth era where the elites begin to think rational in asserting their power. However, it does not have a major impact on the policies to be produced.